Characterization of Primary and Recurrent Nodules in Liver Cirrhosis Using Contrast-Enhanced Ultrasound: Which Vascular Criteria Should Be Adopted? - Leoni, S.; Piscaglia, F.; Granito, A.; Borghi, A.; Galassi, M.; Marinelli, S.; Terzi, E.; Bolondi, L. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To assess the impact of different vascular patterns at contrast-enhanced ultrasound (CEUS) on the characterization of small liver nodules (10 – 30 mm) in cirrhosis and to determine whether primary nodules and recurrent nodules (after a previously treated hepatocellular carcinoma) display variations in enhancement pattern.Materials and Methods: A total of 135 cirrhotic patients were evaluated. A diagnosis of hepatocellular carcinoma (HCC) was established according to AASLD Guidelines, based on imaging (computed tomography and/or magnetic resonance) or liver biopsy. All patients underwent CEUS. Different CEUS patterns were evaluated in terms of diagnostic accuracy: HYPER-HYPO: Arterial hyperenhancement followed by washout (hypoechoic appearance compared with surrounding parenchyma) in late phase; HYPER-ISO: Arterial hyperenhancement followed by isoenhancement (isoechoic appearance) in late phase; ISO-ISO: Isoenhancement in all vascular phases.Results: A total of 155 consecutive primary (n = 90) or recurrent (n = 65) nodules were detected. HCC was diagnosed in 127 nodules (71 primary, 56 recurrent). A characteristic HYPER-HYPO CEUS pattern was revealed in 52/127 (40.9 %) HCCs (31 primary, 21 recurrent) giving a positive predictive value (PPV) of 98 % (97 % primary, 100 % recurrent) and an accuracy of 51 % (54 % primary, 46 % recurrent). A HYPER-ISO pattern was noted in 46 HCCs (31 primary, 15 recurrent). Assuming this pattern to also be indicative of HCC, the PPV and accuracy were 94 % (93 % primary, 97 % recurrent) and 77 % (84 % primary, 68 % recurrent), respectively. An ISO-ISO pattern was present in 29 HCCs (9 primary, 20 recurrent) and 22 non-HCCs (14 primary, 8 recurrent).Conclusion: These data confirm that the HYPER-HYPO pattern at CEUS is definitely diagnostic for HCC in cirrhosis and that the HYPER-ISO pattern has a similar PPV, indicating that this pattern is highly suspicious for HCC. The ISO-ISO pattern was found in > 50 % of recurrent nodules and indicates a high risk of HCC.
Keywords: hepatocellular carcinoma; cirrhosis; contrast-enhanced ultrasound; washout